Síntese de micro / nanopartículas de óxido de cálcio por queima de alginato usando via verde - Araújo, Patrícia dos Santos (Universidade Federal de São Carlos, 2018)
The present study describes the synthesis of micro / nanoparticle by the method of combustion of alginate associated with ions through gelling, verifying if the properties of the metallic oxides can be influenced by gelation conditions and mechanism of degradation from different conditions of thermal treatment. Experiments were carried out with Sodium and Calcium alginate in thermogravimetric analysis, with a heating rate of 10 °C.min-1 and 50 °C.min-1 in atmosphere of synthetic air and with the burning of the calcium alginate in the oven muffle with heating rate of 10 ° C.min-1 and 20 ° C.min-1 and 15 minutes isotherm at the end of the process. Samples were collected at intermediate temperatures and at the end of degradation. The obtained samples were characterized using scanning electron microscopy, infrared vibrational spectroscopy and X-ray diffraction. It was verified through the obtained thermoanalytical curves that the degradation process can be divided into three main stages, and the sodium alginate yielded - at the end of the degradation - a residue percentage higher than that obtained in the burning of the calcium alginate under the same conditions. Samples observed by scanning electron microscopy presented porous structures, micro and nanometric particles size. In the study of diffraction, it was observed that during the burning phases, the material changed from a predominantly amorphous structure, to form crystalline structures such as Ca(OH)2, CaCO3 in the calcite phase and CaO in the final stages. These results demonstrate the potential of the project in controlling the final product obtained by the combustion method to obtain metal oxide particles according to the characteristics desired for certain applications.
Green synthesis of calcium oxide micro/nano particles by alginate template
Keywords: Alginato; Degradação; Gelificação; Óxidos Metálicos; Micro/Nanopartículas; Cal - Combustão; Lime - Combustion; CIENCIAS EXATAS E DA TERRA::QUIMICA